LEGAL REGULATION OF RELATIONS BETWEEN THE UKRAINIAN PARLIAMENT COMMISSIONER FOR HUMAN RIGHTS AND PUBLIC ADMINISTRATION BODIES - Bagmet, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: the article is dedicated to a comprehensive analysis of the legislative regulation of the interaction between the Ukrainian Parliament Commissioner for Human Rights (Ombudsman) and public administration bodies. The main objective is to identify normative gaps and contradictions that impede the effective implementation of parliamentary control in the sphere of human rights protection. Additionally, the research aims to formulate practical recommendations for improving the legal mechanism governing interactions between the Ombudsman and government bodies, which will enhance the overall level of protection and enforcement of human rights in the context of contemporary challenges, such as digital transformation, decentralization reform, and international integration. Research methods: a comprehensive methodological approach has been applied, encompassing formal-legal analysis of legislative and regulatory acts of Ukraine (including the Constitution of Ukraine, the Law of Ukraine "On the Ukrainian Parliament Commissioner for Human Rights" dated December 23, 1997, No. 776/97-VR), as well as administrative-legal regulations. Comparative legal analysis was employed to examine international human rights standards, including the Universal Declaration of Human Rights (1948), the European Convention on Human Rights (1950), and the Paris Principles ("Principles relating to the Status of National Institutions for Human Rights") approved by the Vienna World Conference on Human Rights and the UN General Assembly in 1993. The statistical method was used to evaluate the effectiveness of human rights activities based on official data published by the Ombudsman’s Office. Additionally, logical and systemic methods were employed to develop conclusions and recommendations. Results: the conducted analysis revealed several systemic deficiencies within the legal framework governing the activities of the Ombudsman. These primarily include insufficiently imperative powers granted to the Ombudsman, ineffective sanction policies (fines ranging from 100 to 200 non-taxable minimum incomes), unclear procedures for communication and cooperation with public authorities, and the lack of mandatory implementation of the Ombudsman’s recommendations in the legislative drafting process. Examination of statistical data for 2023 demonstrated the considerable scale of the Ombudsman’s activities (over 19,000 inquiries, 188 formal submissions, and more than 3,000 monitoring visits), yet the low implementation rate of recommendations indicates significant limitations in the institution’s actual influence on remedying human rights violations. Discussion: to address these identified problems, specific legislative improvements have been proposed. In particular, the research substantiates the necessity of legally defining the concept of the "Ombudsman’s inquiry" with imperative force, significantly increasing fines for non-compliance with lawful requirements of the Ombudsman, granting the Ombudsman the authority to initiate disciplinary and criminal proceedings in cases of serious human rights violations, and formalizing the obligatory participation of the Ombudsman in legislative drafting processes. Implementing these changes has the potential to significantly strengthen parliamentary oversight and enhance the effectiveness of the Ombudsman’s activities, thereby positively impacting the overall state of human rights protection in Ukraine.